Functional Outcomes After Total Hip Arthroplasty for the Acute Management of Acetabular Fractures: 1- to 14-Year Follow-up. Issue 3 (March 2015) - Lin, Carol; Caron, Jason; Schmidt, Andrew H.; Torchia, Michael; Templeman, David
Abstract : Objective: This study reports the complications and functional outcomes in patients treated acutely with combined open reduction internal fixation (ORIF) and immediate total hip arthroplasty (THA) for displaced comminuted acetabular fractures. Design: Single surgeon retrospective case series. Setting: Level 1 trauma center. Patients: Thirty-three consecutive patients (18 women; mean age, 66 years) from 1996 to 2011 with an average follow-up of 5.6 years (range, 1–14.3 years) were included in this study. Intervention: ORIF and immediate THA. Main Outcome Measurements: Oxford Hip Score and reoperation. Methods: All patients had at least 1 year of telephone or clinical follow-up. Postoperative complications, reoperations, and available radiographs were reviewed. Results: Six patients died of causes unrelated to their injuries or surgery; before death, these patients had well-functioning hips. There was a 15% complication rate. At last follow-up, 94% of hips remained in situ and were functioning well. The average Oxford Hip Score at final follow-up was 17 (range, 12–32), with 93% of patients reporting good to excellent function. There was no statistical association between fracture type, age, or fixation type and outcome. Conclusions: Acute ORIF and immediate THA for selected acetabular fractures is a safe viable treatment option with good to excellent functional outcomes and may reduce the need for 2 separate operations in many patients. Functional outcomes are equivalent to those after primary THA for osteoarthritis. This study does not address at which age acute THA is a cost-effective treatment option. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.